Impacts of conservation activities on people who are incarcerated: a case study based on qualitative and quantitative analyses - Nalini M. Nadkarni; Jacqueline M. Chen; Jeremy S. Morris; Amanda E. Carriero; Thomas N. Kaye; Kelli Bush; Megan Young; Laura George (Ecology and Society, 2022)
In the past two decades, conservationists and the corrections sector have implemented collaborative ecological restoration projects, creating more inclusive arenas for conservation. These venues provide people who are incarcerated with opportunities to have a positive impact on their environment, and for ecologists to communicate science and the importance of nature with people in nature-deprived environments. We provide examples of conservation programs and their associated media pieces nationwide, whose descriptions, to date, have been almost entirely anecdotal and without formal evaluation. In this study, a collaboration of ecologists and social scientists analyzed impacts on the “incarcerated citizen scientists” who participated in two conservation projects coordinated by these ecologists at the Salt Lake County Jail, Utah, using quantitative and qualitative approaches, including voluntary pre- and post-surveys. The quantitative results informed potential outcomes, but were inconclusive. However, the qualitative results revealed that a majority of the participants reported gaining knowledge about science and conservation, and that about a quarter of them reported psychological benefits from participating, such as feeling that they were able to give back to their community through the project. These results document the potential positive impacts that participation in ecological restoration projects can help promote well-being and community involvement, and to increase science knowledge from all participants. The results also reinforce the importance of collaborations between scientists who use quantitative and qualitative approaches and analytical tools, which, when combined, provide the capacity to measure, analyze, and interpret data from human participants. These considerations should be further explored with collaborations of natural scientists, social scientists, corrections staff, and people who are incarcerated as ecological restoration projects in correctional institutions become more prevalent.